As mulheres não tão silenciosas de Roma: representações do feminino em Plínio, o Jovem (62 a 113 d.C) - Mennitti, Danieli [UNESP] (2015)
This research aims to understand feminine's representations in trajanic literature, by feminist and gender theories, between 62 AD - 113 AD. These representations are analyzed with the aim of promoting a historiographical review on the Roman women. The main objective is to analyze the representation of social and cultural roles exercised by roman women, being these compiled by men, under the assumptions of a patriarchal and masculine society